Recent Progress of Supercontinuum Generation in Nanophotonic Waveguides. Issue 1 (3rd December 2022) - Fang, Yuxi; Bao, Changjing; Li, Si‐Ao; Wang, Zhi; Geng, Wenpu; Wang, Yingning; Han, Xu; Jiang, Jicong; Zhang, Weigang; Pan, Zhongqi; Li, Zhaohui; Yue, Yang
Abstract: Supercontinuum (SC) has opened up possibilities for numerous applications in optical communications, signal processing, metrology, and spectroscopy. Supercontinuum generation (SCG) in the integrated nonlinear platforms has attracted much interest recently, due to its fundamental advantages in terms of complementary metal oxide semiconductor compatibility, low power consumption, compact size, and cost‐effectiveness. In this paper, the latest progress on various types of nanophotonic waveguides for SCG is reviewed. The material properties of silicon, germanium, silicon–germanium alloy, silicon nitride, silica, chalcogenide, III–V materials, lithium niobate, and other materials, which are used as nonlinear media for SCG are discussed. The wavelength‐dependent nonlinear Kerr index, material, and nonlinear loss of the waveguides are taken into account. This review mainly focuses on the SCG resulting from the cubic χ (3) nonlinearity processes pumped by the femtosecond pulse. The recent representative SCG works based on the integrated optical waveguides are summarized, and further classified according to the dispersion characteristics. Furthermore, different types of spectra broadening mechanisms in details according to the classifications are analyzed. Perspectives on the SC spectral coverage, the realization of various dispersion curves, and the novel materials, which are the key aspects of the SCG in nanophotonic waveguides are provided. Abstract : Latest progresses on various types of nanophotonic waveguides for supercontinuum generation (SCG) are reviewed. Material properties of nonlinear media for SCG are discussed. Recent representative SCG works based on the integrated optical waveguides are summarized and further classified according to the dispersion characteristics. Different types of spectra broadening mechanisms are analyzed in details accordingly.